Low Temperature Characteristics of Ge-on-Si Waveguide Photodetectors: A Combined Simulation and Experimental Study - Jingchuan Liu; Zhenyu Li; Xiaofei Liu; Wentao Yan; Xingyan Zhao; Shaonan Zheng; Yang Qiu; Qize Zhong; Yuan Dong; Ting Hu (Micromachines)
Benefiting from the progress of the germanium (Ge) epitaxy process on silicon (Si) substrates, waveguide-integrated Ge-on-Si photodetectors (PDs) have demonstrated decent performances in short-wave infrared (SWIR) detection. By lowering the operating temperature, theses PDs can meet the stringent signal-to-noise requirements for high-sensitivity detection. We systematically investigated the dark current characteristics and optical response in the 1500–1600 nm wavelength range of the waveguide-integrated Ge-on-Si PDs operated at low temperatures (200 K to 300 K). Under a −3 V bias, the PD exhibits a room-temperature dark current of 4.62 nA and a responsivity of 0.87 A/W at 1550 nm. When the temperature was reduced to 200 K, the dark current decreased to 93.69 pA, and the responsivity dropped to 0.34 A/W. Using finite-difference time-domain (FDTD) and technology computer-aided design (TCAD) simulations, we extracted the absorption coefficients of epitaxial Ge on Si at low temperatures. At room temperature, the absorption coefficient at the wavelength of 1550 nm was approximately 1100 cm−1, while at 200 K, the absorption coefficient decreased to 248 cm−1. The outcomes of this work pave the way for the high-performance low-temperature Si photonic systems in the future.